Rainforest Reforestation and Biodiversity Benefits: A Case Study from the Australian Wet Tropics - Harrison, Robert; Wardell-Johnson, Grant; McAlpine, Clive (Annals of Tropical Research, 2003)
This paper examines the effectiveness of a rainforest reforestation program (the Community Rainforest Reforestation Program in north-eastern Queensland, Australia) in providing amenity and biodiversity benefits. This program involved small areas of mainly mixed native timber species on private farmland. Government support was provided for the program, for both timber production and environmental reasons. Survey results reveal that landholders have planted trees, and intend to manage plantations, for diverse reasons, including conservation purposes. Tice plantings appear to be of environmental value, forming wildlife corridors and buffer areas. In this respect, the CRRP has achieved a limited success in meeting the implicit goal of biological conservation.